Appropriate Thai High School Student Internet Behaviour: A Hierarchical Linear Model Analysis - Punnee Leekitchwatana; Paitoon Pimdee (My University, 2017)
The research used a hierarchical linear model to develop a model to study the variables of appropriate Internet use of 2,400 Thai high school students from 48 high schools. Furthermore, the groups were divided into one group of 1,200 students in science related programs, while the second group of 1,200 students were in a non-science related program. The data collection instrument was a reliability questionnaire which was determined to range between 0.75-0.97. Data were analysed using statistical averages, standard deviation, and analysis of hierarchical linear models (HLM). The research found that Thai high school students have appropriate Internet use behaviour at a very appropriate level, while the HLM of appropriate Internet use behaviour of students contained two predictive variables at both the student level and school level. These included the four student predictive variables of ability, characteristic, family, and student grade point average (GPA). At the school level in the HLM, there were two predictor variables including friends and schools, which had a direct influence and an indirect influence, respectively. There were also six capacity variables having both positive influence and statistical significance.
Keywords: Variables; Statistical Analysis; Impact of Technology on Adolescents